Ensuring Justice: An In-depth Analysis of Witness Protection in Divorce Cases within the Religious Court in Indonesia - Muh Sutri Mansyah; Rizki Mustika Suhartono; Rasmala Dewi; Sajida Humaira; Kisty Lee (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The aim of this research is to analyze witness protection in divorce cases in Indonesia. Witnesses are one of the pieces of evidence used in divorce cases in the Religious Court, yet witnesses brought forth during trials face threats and legal demands. Meanwhile, the aspect of witness protection remains unregulated. This article questions why it is crucial to protect witnesses in divorce cases in religious courts and what constitutes an ideal concept of witness protection. This research employs a legislative and case-based approach. This article suggests that witness protection is highly significant as witnesses are often utilized as evidence. Based on 709 applications from non-criminal cases seeking protection from the Witness and Victim Protection Agency, it is evident that the Witness and Victim Protection Act only regulates witnesses in criminal offenses. It extends beyond the interests of the petitioner and the respondent. Yet, it has to be in the interest of the witnesses and the court so as to achieve truth and justice. Simply speaking, the protection of witnesses should be regulated under the Witness and Victim Protection Act.